Czynniki determinujące ewolucję polityki fiskalnej w Polsce - Pająkiewicz, Józef (Determiners of the evolution of the Polish fiscal policy, 2006)
Monetary and fiscal policies are main instruments that governments can use to control economic processes. Their nature and evolution result from interaction of internal and external circumstances affecting the national economy. At the onset of economic transformation in Poland, the introduction of restrictive monetary and fiscal policies was determined by the need to halt a rocketing inflation. Bringing down the inflation, the need for stimulating economic growth and the reform of public finances have resulted in gradual removal ofthe restrictions in monetary policy, but also in the necessity to tighten the fiscal policy. Such an evolution line of fiscal policy has also been rooted in the need to adjust public finances in Poland to European standards.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1129, s. 208-214